Question
upstudy study bank question image url

Let \( h(x)=x+9 \) and \( g(x)=\sqrt{x-6} \). Find \( (h-g)(-1) \). Select the correct choice below and fill in any answer boxes within your choice. A. \( (h-g)(-1)=\square \) (Simplify your answer. Type an integer or a fraction.) B. The function value does not exist.

Ask by Bright Hanson. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The function value does not exist.

Solution

We are given h(x) = x + 9 and g(x) = √(x – 6). To find (h – g)(-1), we compute:  h(-1) = -1 + 9 = 8.  g(-1) = √(-1 – 6) = √(-7). Since √(-7) is not a real number, g(-1) is undefined in the real number system. Therefore, (h – g)(-1) is undefined. The correct choice is B. The function value does not exist.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find \( (h-g)(-1) \), we first need to compute \( h(-1) \) and \( g(-1) \). \( h(x) = x + 9 \) So, \( h(-1) = -1 + 9 = 8 \). Now for \( g(x) = \sqrt{x - 6} \): Since \( -1 - 6 = -7 \), this means \( g(-1) = \sqrt{-7} \), which is not a real number. Now, we can compute \( (h-g)(-1) \): \[ (h-g)(-1) = h(-1) - g(-1) = 8 - \text{(not defined)} \] Thus, the correct choice is: B. The function value does not exist.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy